TYPIFICATIONS IN CHROMOLAENA AND PRAXELIS (ASTERACEAE: EUPATORIEAE) - Christ, Anderson Luiz; Ritter, Mara Rejane (Phytotaxa, 2018)
The genera Chromolaena Candolle (1836: 133) and Praxelis Cassini (1826: 261) (Asteraceae: Eupatorieae) were both segregated from Eupatorium Linnaeus (1753: 836) in 1970 (King & Robinson 1970a, 1970b). Despite several taxonomic studies (including new combinations and typifications) since then, there are still countless names that need to be typified. As a result of our ongoing taxonomic treatment of both genera in the state of Rio Grande do Sul, Brazil, we propose here five lectotypes and one neotype in Chromolaena and one lectotype in Praxelis.